Use of gravitational waves to probe the formation channels of compact binaries - Vitale, Salvatore; Lynch, Ryan; Sturani, Riccardo [UNESP]; Graff, Philip (Iop Publishing Ltd, 2017)
With the discovery of the binary black hole coalescences GW150914 and GW151226, the era of gravitational-wave astrophysics has started. Gravitational-wave signals emitted by compact binary coalescences will be detected in large number by LIGO and Virgo in the coming months and years. Much about compact binaries is still uncertain, including some key details about their formation channels. The two scenarios which are typically considered, common envelope evolution and dynamical capture, result in different distributions for the orientation of the black hole spins. In particular, common envelope evolution is expected to be highly efficient in aligning spins with the orbital angular momentum. In this paper we simulate catalogs of gravitational-wave signals in which a given fraction of events comes from common envelope evolution, and has spins nearly aligned with the orbital angular momentum. We show how the fraction of aligned systems can be accurately estimated using Bayesian parameter estimation, with 1 sigma uncertainties of the order of 10% after 100-200 sources are detected.
Keywords: gravitational waves; common envelope evolution; spin alignment; compact binaries